2004
DOI: 10.1016/s1350-4533(03)00137-1
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of magnetic resonance images using a combination of neural networks and active contour models

Abstract: Segmentation of medical images is very important for clinical research and diagnosis, leading to a requirement for robust automatic methods. This paper reports on the combined use of a neural network (a multilayer perceptron, MLP) and active contour model ('snake') to segment structures in magnetic resonance (MR) images. The perceptron is trained to produce a binary classification of each pixel as either a boundary or a non-boundary point. Subsequently, the resulting binary (edge-point) image forms the externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…To overcome the limitations of the semi or fully automated segmentation method by using ANN, hybrid methods have also been proposed. Reddick et al suggested the combination of SOM and ANN for brain image segmentation [27], and Middleton et al proposed a different approach combining ANN and active contour model [21] . A hybrid method of wavelet with ANN has also been introduced [18].…”
Section: Segmentation Methods With Artificial Neural Networkmentioning
confidence: 99%
“…To overcome the limitations of the semi or fully automated segmentation method by using ANN, hybrid methods have also been proposed. Reddick et al suggested the combination of SOM and ANN for brain image segmentation [27], and Middleton et al proposed a different approach combining ANN and active contour model [21] . A hybrid method of wavelet with ANN has also been introduced [18].…”
Section: Segmentation Methods With Artificial Neural Networkmentioning
confidence: 99%
“…In another attempt, a modelmatching method was used to segment the lung parenchyma by registering individual images to a model created from manually segmented training dataset (Lelieveldt et al, 1999). Other approaches involved a combination of supervized neural network classifier and parametric active contour (Middleton and Damper, 2004). Another approach that incorporated merging of multiple parametric active contour within homogeneous regions (Ray et al, 2003) was also piloted to automatically segment the lung parenchyma.…”
Section: Previous Studiesmentioning
confidence: 99%
“…For example, some of these approaches require substantial runtimes (Kirby et al, 2012a;Lelieveldt et al, 1999) while others were restricted to certain region of interest (Ray et al, 2003) or dependent on robust grey level thresholding (Sensakovic et al, 2006;Tustison et al, 2010;Woodhouse et al, 2005). Finally, other approaches required a substantial amount of user interaction (Kirby et al, 2012a), extensive training and frequent updating with careful expert manual segmentation (Middleton and Damper, 2004;Tustison et al, 2011).…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore here we make a brief overview of the methods available. Detailed reviews on image segmentation techniques can be found in the literature (Freixenet et al, 2002;Pal and Pal, 1993;Gonzalez and Woods, 1992;Deklerck et al, 1993;Freixenet, 2002;Russ, 2002), with the most popular methods being thresholding (Gommes et al, 2003;Otsu, 1979), split-and-merge (Manousakas et al, 1998;Deklerck et al, 1993), region growing (Lu et al, 2003;Hojjatoleslami and Kittler, 1998), clustering (Patino and Razaz, 2001), watershed segmentation (Razaz and Hayard, 2000), snakes (Middleton and Damper, 2004;Ngoi and Jia, 1999) and edge-detection-based methods (Rajab et al, 2004;Pavlidis and Liow, 1990). Some applications of these methods have been based on a colour segmentation scheme (Onyango and Marchant, 2003;Derganc et al, 2003), but nevertheless crystals generally show a translucent and colourless appearance and therefore the segmentation is better suited in grey scale.…”
Section: Image Analysismentioning
confidence: 99%